Effects of sediment smothering on the sponge holobiont with implications for dredging management - Mari-Carmen Pineda (Nature Portfolio, 2017)
Abstract One of the ways dredging can affect benthic habitats is through high levels of sediment deposition, which has the potential to smother sessile organisms such as sponges. In order to provide pressure-response values to sedimentation and tease apart the different cause-effect pathways of high turbidity, 5 sponge species, including heterotrophic and phototrophic nutritional modes, were exposed for up to 30 d to multiple sediment deposition events, each of which resulted in an initial covering of 80–100% of the surface of the sponges in a layer ~0.5 mm thick. The response of the sponges was examined using a suite of different response variables including growth, respiration, lipid content, community composition of the microbial symbionts, and maximum quantum yield and chlorophyll content of the phototrophic symbionts. Different species showed different mechanisms of sediment rejection and different patterns of sediment clearance. All species survived the treatments, were able to tolerate high levels of partial covering of their surfaces, and for most species the treatment did not alter the health of the sponge holobiont. Results from this study will guide interpretation of experiments examining the combined effects of all three dredging-related pressures, and aid the development of water quality thresholds for impact prediction purposes.